Diagnostics of enterprise selection criteria in the public e-procurement system - Klyuvak, Oksana; Skrynkovskyy, Ruslan (Technology audit and production reserves, 2017)
The integrated complex system with subsystems of e-logistics, e-document flow, budgeting, payments and invoices of the subjects of procurement of goods, works, services for public funds, taking into account the criterion of «price» and non-price criteria for selecting the winner, is improved in the article. The classification of non-price criteria for selecting the winner of procurement, which are dictated by the European Union law, namely of: technical, resource and competency, safety and quality, reputation and image, and basic. Recommendations are proposed to improve the procedure for selecting enterprises related to security features and the quality of the tender proposal, strengthening the role of technical experts in tender committees, listing of public documents and deadlines for pre-threshold procurement. An essential part of the economic and mathematical model of diagnostics of selection criteria for public e-procurement enterprises is developed on the basis of determining the balance of interests of the supplier and the customer, the customer price correction coefficient, taking into account the proposed classification of non-price selection criteria, the price coefficient of the subject of e-procurement of the supplier, taking into account business processes leading to economic and social effects, and input settings «information-time opportunities/threats of resources», the covariance between the values of costs for providing an optimum level of non-price criteria for selecting the winner of procurement performance and indicators of participation in public e-procurement.